A minimally invasive thrombotic model to study stroke in awake mice - Kimberly Marks; Sung-Ji Ahn; Ninamma Rai; Antoine Anfray; Costantino Iadecola; Josef Anrather (Nature Communications)
Abstract Experimental stroke models in rodents are essential for mechanistic studies and therapeutic development. However, these models have several limitations negatively impacting their translational relevance. Here we aimed to develop a minimally invasive thrombotic stroke model through magnetic particle delivery that does not require craniotomy, is amenable to reperfusion therapy, can be combined with in vivo imaging modalities, and can be performed in awake mice. We found that the model results in reproducible cortical infarcts within the middle cerebral artery (MCA) territory with cytologic and immune changes similar to that observed with more invasive distal MCA occlusion models. Importantly, the injury produced by the model was ameliorated by tissue plasminogen activator (tPA) administration. We also show that MCA occlusion in awake animals results in bigger ischemic lesions independent of day/night cycle. Magnetic particle delivery had no overt effects on physiologic parameters and systemic immune biomarkers. In conclusion, we developed a novel stroke model in mice that fulfills many requirements for modeling human stroke.